2022
DOI: 10.1111/cfs.12867
|View full text |Cite
|
Sign up to set email alerts
|

Family well‐being during the COVID‐19 lockdown in Italy: Gender differences and solidarity networks of care

Abstract: During the COVID-19 pandemic, families experienced new challenges related to reorganizing living spaces and the need to renegotiate domestic and care roles. This paper aims to understand how Italian families have reacted to this situation with respect to psychological well-being, the management of domestic and care activities and solidarity networks of care. The participants were 560 Italian subjects who reported having a parental role. The protocol included a measure of well-being (the General Health Question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…It emerged that it was important during life with COVID to maintain one’s hobbies and passions or to practice new ones even in the company of significant others, especially family members: gardening, cooking, and painting were some examples of how people got active and had experimented with new activities for their physical and mental well-being. In this regard, a previous research highlighted how the family, as an instrument that generates trust in the other, in its adherence to the rules of protection and containment of viruses, represents the most functional group of mutual protection from contagion (Rania et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It emerged that it was important during life with COVID to maintain one’s hobbies and passions or to practice new ones even in the company of significant others, especially family members: gardening, cooking, and painting were some examples of how people got active and had experimented with new activities for their physical and mental well-being. In this regard, a previous research highlighted how the family, as an instrument that generates trust in the other, in its adherence to the rules of protection and containment of viruses, represents the most functional group of mutual protection from contagion (Rania et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It goes without saying that the exceptional situation created by the COVID-19 pandemic has had a significant impact on families and the way they live together [ 26 ]. It is even possible to hypothesize that the forced limitation of youth mobility could have effects on their longer-term mobility, particularly in relation to the usual flows of youth leaving or returning to the family home [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…We indicated that mothers and fathers in the postpartum period did not differ in COVID-19-related life changes concerns. Given that 97% of the sample was married, the similarity between maternal and paternal COVID-19-related concerns may be explained by the fact that, after the birth of a child, both new mothers and fathers experience similar changes in their daily lives and couples’ common experiences mutually influence one another due to their shared interdependence [ 50 , 51 , 52 ]. Parents had relatively high levels of perceived family functioning, dyadic coping and perceived social support, while depressive symptoms were low to midrange for the majority of them.…”
Section: Discussionmentioning
confidence: 99%